2023
DOI: 10.1002/mds.29375
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Density and Glucose Consumption in Patients with Lewy Body Diseases: An [11C]UCB‐J and [18F]FDG PET Study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 58 publications
0
8
1
Order By: Relevance
“…Understanding the association between BP ND and R 1 longitudinally would help to unravel which comes first, and whether this changes as the disease progresses. Further, in our study we observed a higher magnitude of synaptic loss than losses in relative brain perfusion (compared to controls), while a previous study with [ 11 C]UCB-J and [ 18 F]FDG PET in Parkinson’s disease cohort with and without dementia observed a higher loss in metabolism 32 . This could be an example where glucose metabolism is more sensitive than blood flow but can also be caused due to dissociation between glucose metabolism and blood flow 33 .…”
Section: Discussioncontrasting
confidence: 69%
“…Understanding the association between BP ND and R 1 longitudinally would help to unravel which comes first, and whether this changes as the disease progresses. Further, in our study we observed a higher magnitude of synaptic loss than losses in relative brain perfusion (compared to controls), while a previous study with [ 11 C]UCB-J and [ 18 F]FDG PET in Parkinson’s disease cohort with and without dementia observed a higher loss in metabolism 32 . This could be an example where glucose metabolism is more sensitive than blood flow but can also be caused due to dissociation between glucose metabolism and blood flow 33 .…”
Section: Discussioncontrasting
confidence: 69%
“…The SUVR1 decrease matched well with volumetric changes and the SUVR1 levels in frontal cortex correlated with cognitive function ( Andersen et al, 2021 ). However, in a follow-up study by the same groups, changes in 18F-FDG exceeded those observed in 11C-UCB-J PET ( Andersen et al, 2023 ). This discrepancy could imply that both changes represent distinct facets of the pathogenesis, rendering 11C-UCB-J PET a complementary tool in the evaluation of LBD.…”
Section: Sv2a Pet In Neurodegenerative Diseasesmentioning
confidence: 86%
“…In patients with DLB, synaptic loss was observed in substantia nigra, occipital, parietal and frontal cortices but not in medial temporal regions such as hippocampus and amygdala [ 48 ]. In a direct comparison of 11 C-UCB-J and 18 F-FDG in DLB patients, the magnitude as well as spatial extent of hypometabolism exceeded that of synaptic loss [ 75 ]. As for FTD, decreased synaptic density was most prominent in frontal regions and to a somewhat lesser extent also in temporal regions, insula and anterior cingulate [ 44 ].…”
Section: Discussionmentioning
confidence: 99%